Analysis and modelling of the characteristics of telecommunication antennas utilising metamaterials with a circular structure - Defrianto, Defrianto; Saktioto, Saktioto; Anita, Sofia; Zahroh, Siti; Soerbakti, Yan; Emrinaldi, Tengku (Indonesian Physics Communication, 2024)
The development of telecommunication antenna technology is increasingly being considered with the need for high and practical antenna performance. The antenna technology can be realized by using the split ring resonator (SRR) metamaterial structure. SRR metamaterial is a periodic material that has minimal manufacturing dimensions and is able to work at high frequencies. The ability of this metamaterial has the potential to be implemented in microstrip antenna structures as telecommunication applications. This study aims to design, simulate and analyze the characteristics of SRR-Circle metamaterials against the frequency function and application performance as a telecommunication antenna. The process is carried out using the Computer Simulation Technology (CST) Studio Suite Software which is operated at a working frequency of 0.009 – 9 GHz. The metamaterial structure is combined from 1 – 4 SRRs in the shape of a Circle with a fixed radius of 3.5 mm. The results of this study indicate the characteristics of metamaterials with negative values in relative permittivity (ɛᵣ), relative permeability (μᵣ) and refractive index (n) with the highest values in the metamaterial structure of the combination of 4 SRR-Circles, each with values of -144.33 Farad/m, -9.29 H/m and -9.07. In its application as a telecommunications antenna, metamaterials have succeeded in improving antenna performance. The highest antenna performance was obtained in the combination structure of 4 SRR-Circles with a return loss value of -34.37 dB, and a bandwidth of 1.00 GHz at a VSWR of 6.77 – 7.77 GHz. The results of this antenna performance have the potential to be applied to telecommunications antenna technology such as satellites, radars and 5G networks.